Indonesian progressive Muslims and the discourse of the Israeli-Palestinian peace: Soekarno’s, Abdurrahman Wahid’s and Ahmad Syafii Maarif’s thoughts - Hasnan Bachtiar; Muneerah Razak; Soni Zakaria (Universitas Negeri Yogyakarta, 2021)
Indonesia, as one of the largest majority Muslim countries, has had a consistent stance on the Israel-Palestine conflict since its inception. Despite the general pro-Palestinian stance, this article explores the discourse of three significant leaders of the Indonesian people - Soekarno, Abdurrahman Wahid and Ahmad Syafii Maarif. As presidents of Indonesia of different time periods of Indonesia, Soekarno and Wahid tended to be pragmatic in their articulation of their political stances, though it is articulated in different ways. Maarif, as the leader of Muhammadiyah, a popular non-governmental organisation on the ground, was more idealistic and concerned with anti-Zionism. This article highlights that the different nuances of the three leaders is due to their different capacities as leaders, their social and political contexts, and the intellectual leanings and experiences.